Low-complexity robust multi-cell MISO downlink precoder design - Medra, Mostafa; Davidson, Timothy N. (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2016)
This paper develops low-complexity design techniques for robust linear precoders suitable for various multi-cell multiple-input single-output (MISO) downlink systems. The goal is to satisfy pre-specified SINR requirements for users in multiple cells under some base station power constraints, in the absence of perfect channel state information (CSI). First, we consider the case of full cooperation between base stations and derive a simple iterative algorithm that achieves the required SINRs with high probability despite the presence of channel uncertainties. Then we consider the case of distributed coordination between base stations and develop a simple iterative algorithm that requires only very limited communication among the base stations. Our simulation results demonstrate that substantial robustness can be obtained at a low computational cost.